2016
DOI: 10.1016/j.agee.2015.11.011
|View full text |Cite
|
Sign up to set email alerts
|

Simulating long-term impacts of cover crops and climate change on crop production and environmental outcomes in the Midwestern United States

Abstract: It is critical to evaluate conservation practices that protect soil and water resources from climate change in the Midwestern United States, a region that produces one-quarter of the world's soybeans and one-third of the world's maize. An over-winter cover crop in a maize-soybean rotation offers multiple potential benefits that can reduce the impacts of higher temperatures and more variable rainfall; some of the anticipated changes for the Midwest. In this experiment we used the Agricultural Production Systems… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
104
0
2

Year Published

2017
2017
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 180 publications
(110 citation statements)
references
References 71 publications
4
104
0
2
Order By: Relevance
“…The warmer winter temperatures also accelerated heat unit accumulation and curbed temperature stress. Basche et al (2016) found that warmer temperatures contributed to increasing biomass of future rye cover crops in Iowa, compared to current conditions. Relative to the baseline, the biomass of wheat, barley, and rye increased by 24% (B1) and 58% (A2), by 12% (B1) and 43% (A2), and by 7% (B1) and 37% (A2), respectively.…”
Section: Winter Cover Crop Biomassmentioning
confidence: 99%
“…The warmer winter temperatures also accelerated heat unit accumulation and curbed temperature stress. Basche et al (2016) found that warmer temperatures contributed to increasing biomass of future rye cover crops in Iowa, compared to current conditions. Relative to the baseline, the biomass of wheat, barley, and rye increased by 24% (B1) and 58% (A2), by 12% (B1) and 43% (A2), and by 7% (B1) and 37% (A2), respectively.…”
Section: Winter Cover Crop Biomassmentioning
confidence: 99%
“…In other regions of North America and the Caribbean, declining yields are expected according to PĂ©rez and Omar (2015), in North Africa declining wheat, according to Chourghal et al (2016), corn in the United States (from 1.6 to 2.7% per decade) according to Basche et al (2016), as well as in some regions of Europe where there will be an increase in the frequency of extreme events and population of the continent (Trnka et al, 2015).…”
Section: Impact Of Climate Change On Yield and Quality Of Basic Cerealsmentioning
confidence: 99%
“…The WOFOST model of quantitative analysis of annual crop production based on physio-ecological processes considers phenology, transpiration, respiration, CO 2 absorption, water simulation and daily growth. Basche et al (2016) analyzes the Simulator model of Agricultural Production Systems (APSIM), simulate the behavior of the production of corn in winter for a period of 45 years, associating temperature variability to decreased performance per decade. The deterministic mathematical model AquaCrop simulates the development of corn cultivation for various regions of the world, considers total and deficit irrigation, determines optimal planting dates, and simulates biomass and yield according to water availability (Bernal et al, 2013).…”
Section: Traditional Technological Strategiesmentioning
confidence: 99%
“…Over the past years the APSIM model has been successfully applied in this region to simulate production (Hammer et al, 2009;Archontoulis et al, 2014a, b;Dietzel et al, 2016;Puntel et al, 2016;Jin et al, 2017) and environmental aspects of US Midwestern corn and soybean cropping systems (Malone et al, 2007;Archontoulis et al, 2016a, b;Basche et al, 2016;Martinez-Feria et al, 2016).…”
Section: The Apsim Model Description and Configurationmentioning
confidence: 99%